Lattice solitons in a nonlocal nonlinear medium with self-focusing and self-defocusing quintic nonlinearity - BAĞCI, MAHMUT (IntechOpen, 2022)
The fundamental lattice solitons are explored in a nonlocal nonlinear medium with self-focusing and self-defocusing quintic nonlinearity. The band-gap boundaries, soliton profiles, and stability domains of fundamental solitons are investigated comprehensively by the linear stability spectra and nonlinear evolution of the solitons. It is demonstrated that fundamental lattice solitons can stay stable for a wide range of parameters with the weak self-focusing and self-defocusing quintic nonlinearity, while strong self-focusing and self-defocusing quintic nonlinearities are shortened the propagation distance of evolved solitons. Furthermore, it is observed that when the instability emerges from strong quintic nonlinearity, increasing anisotropy of the medium and modification of lattice depth can be considered as a collapse arrest mechanism.
Keywords: Matematik; Kısmi diferansiyel eşitlikler; Sayısal Analiz; Fizik; Yoğun Madde 2:Elektronik Yapı, Elektrik, Manyetik ve Optik Özellikler; Temel Bilimler; Mathematics; Partial Differential Equations; Numerical Analysis; Physics; Intensive Article 2: Electronic Structure, Electric, Magnetic and Optical Properties; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; MATEMATİK; FİZİK, YOĞUN MADDE; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MATHEMATICS; PHYSICS; MULTIDISCIPLINARY SCIENCES; PHYSICS, CONDENSED MATTER; Multidisipliner; Ayrık Matematik ve Kombinatorik; Yoğun Madde Fiziği; Elektronik, Optik ve Manyetik Malzemeler; Geometri ve Topoloji; Mantık; Fizik Bilimleri; Multidisciplinary; Discrete Mathematics and Combinatorics; Condensed Matter Physics; Electronic, Optical and Magnetic Materials; Geometry and Topology; Logic; Physical Sciences